EFEKTIVITAS PEMBELAJARAN METODE JAS TERHADAP KETERAMPILAN MENULIS TEKS DESKRIPSI SISWA KELAS VI - Sevty Diah Kinanti; Prabawati Nurhabibah; Widia Nur Jannah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low skill of writing descriptive texts of grade VI students of SD Negeri 4 Benda, especially in developing ideas, compiling text structures, using the right vocabulary, and writing the results of observations in a concise and clear manner. The purpose of this study is to determine the effectiveness of the use of the Exploring the Environment method on students' descriptive text writing skills. The problem in this study is the low ability of students to write descriptive texts, so a more innovative and contextual learning method is needed. This study uses a quantitative approach with a pretest-posttest design on 30 students. The research data was collected through a descriptive text writing test before and after the application of the Exploring the Environment method by utilizing the football field as a learning resource. The results of the study showed an increase in students' ability to write descriptive texts as shown by an increase in the average score from 25.63 in the pretest to 71.2 in the posttest. Thus, the Exploring the Environment method is effective in improving the descriptive text writing skills of elementary school students.Top of FormBottom of Form